Linguistic Habitus: The Use of Arabic To Early Childhood In Parenting (Millennial Muslim Parents) - Nur Hamzah; Bayu Suratman; Rahnang Rahnang (AWLADY : Jurnal Pendidikan Anak, 2023)
This paper discusses the use of Arabic among Milinial parents in early childhood care. This study looked at the femomena of arabic use in early childhood by motivated parents and expecting their child to be bilingual and where the child became part of the group's culture. Language is the main medium used in the formation and delivery of cultural meanings and language is a tool and medium used to shape knowledge about the individual and the social world. Language is also related to the arena in which habitus is formed and internalized in language as capital in the form of social practice both consciously and unconsciously using language that has been conceived. It even uses a foreign language to make the individual look different from others and more modern. This research is a qualitative research with a phenomenological approach in analyzing the data obtained. The data collection technique in this study used interviews with millennial families in the upbringing and use of Arabic in early childhood in Pontianak City. This study was conducted to identify phenomena that occur in the millennial family environment in Pontianak City and collect data related to the use of Arabic in early childhood. Furthermore, the author analyzes the data obtained from the data set through the scientific discipline of phenomenology.